2022
DOI: 10.1021/acsestwater.2c00040
|View full text |Cite
|
Sign up to set email alerts
|

Electron Beam Technology Coupled to Fenton Oxidation for Advanced Treatment of Dyeing Wastewater: from Laboratory to Full Application

Abstract: This study developed a novel electron beam (EB) and Fenton process (FP) for the advanced treatment of dyeing wastewater by combining EB radiation with the FP. In the presence of 0.1 mM Fe­(II) and 0.1 mM H2O2, the mineralization efficiency of Rhodamine B was 59.21% at a dose of 2 kGy, which is higher than single EB radiation and the FP, due to the interaction of hydrated electron with Fe­(II) and H2O2, hydrated electron enhanced the activation of H2O2 and the conversion from Fe­(III) to Fe­(II) in the EB radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Electron beam technology, as an ionizing radiation technology, is a new type of advanced oxidation process. , Compared to the conventional advanced oxidation process, ionizing radiation has its own characteristics, such as no demand of chemicals and short process time . Many studies in a laboratory scale have demonstrated that ionizing radiation can remove recalcitrant organic pollutants in the wastewater via the direct action of high energy and the indirect action of reactive species produced by the radiolysis of water molecules (dominant). ,, In addition to laboratory studies, our research group has established full-scale application projects of industrial wastewater treatment including the advanced treatment unit of electron beam irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron beam technology, as an ionizing radiation technology, is a new type of advanced oxidation process. , Compared to the conventional advanced oxidation process, ionizing radiation has its own characteristics, such as no demand of chemicals and short process time . Many studies in a laboratory scale have demonstrated that ionizing radiation can remove recalcitrant organic pollutants in the wastewater via the direct action of high energy and the indirect action of reactive species produced by the radiolysis of water molecules (dominant). ,, In addition to laboratory studies, our research group has established full-scale application projects of industrial wastewater treatment including the advanced treatment unit of electron beam irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…The sole ionizing radiation process as an advanced treatment process usually required a high adsorbed dose that resulted in the increase in treatment cost. The combination of ionizing radiation with the conventional wastewater treatment process could be a way to decrease the adsorbed dose and to simultaneously enhance the removal capacity . The common combined processes have some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…12 The degradation of residual atrazine is thus becoming an urgent issue for environmental protection, especially for water security which is listed as a priority by the "European Green Deal" proposed by the European Commission. The degradation of chemically stable atrazine is challenging, and common water treatment technologies are limited by trace organic concentrations 13 and strict fouling control, 14 so there have been increasing efforts to develop efficient advanced oxidation processes, 3 such as Fenton/Fenton-like oxidation, [15][16][17] ultrasound [18][19][20] and so on. Among them, high voltage electrical discharge (HVED) has attracted more attention because of its advantages, high degradation efficiency and environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%
“…Our research group at Tsinghua University, cooperated with China Guangdong Nuclear Group, successfully researched and developed the electron accelerator and radiation reactor for wastewater treatment, and realized the first application of electron beam technology for the treatment of dyeing wastewater in Jinghua City, Zhejiang Province, in 2016, and established the largest wastewater treatment facility using electron beam technology for the advanced treatment of dyeing wastewater in the world in Jiangmen City, Guangdong Province, in 2019 ( Wang and Wang, 2022a , Wang and Wang, 2022b ). Electron beam technology showed good performance in practical application ( Wang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%